2006
DOI: 10.1007/s00330-006-0527-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis: diagnostic value of nonenhanced CT with selective use of contrast in routine clinical settings

Abstract: The purposes of this study were to determine the (1) frequency with which nonenhanced computed tomography (CT) (NECT) permits conclusive diagnosis of acute appendicitis, (2) accuracy of NECT when findings are conclusive, and (3) overall accuracy of a CT protocol consisting of NECT with selective use of contrast. Five hundred and thirty-six patients underwent a NECT protocol with selective use of contrast. Diagnostic accuracy was then determined separately for (1) patients with conclusive initial NECT, (2) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 32 publications
1
10
2
2
Order By: Relevance
“…Since most children tend to have limited amount of intra-abdominal fat, some believe that this limits the usefulness of nonenhanced CT scans [18], while others believe that the accuracy remains unchanged with varying body mass indexes [19]. One study that directly addressed this issue did not find a significant difference in CT accuracy with varying body mass index [20]. Six of the seven studies in this systematic review included radiologists as investigators and all support the use of noncontrast CT scans for the diagnosis of appendicitis [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 94%
“…Since most children tend to have limited amount of intra-abdominal fat, some believe that this limits the usefulness of nonenhanced CT scans [18], while others believe that the accuracy remains unchanged with varying body mass indexes [19]. One study that directly addressed this issue did not find a significant difference in CT accuracy with varying body mass index [20]. Six of the seven studies in this systematic review included radiologists as investigators and all support the use of noncontrast CT scans for the diagnosis of appendicitis [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 94%
“…enhancement for the diagnosis of acute appendicitis in patients with BMI >18.5, and similar sensitivity and specificity as unenhanced standard-dose CT for detection of alternative diagnoses [33,35], it could constitute a useful tool for the triage of patients with suspicion of appendicitis towards standard i.v. enhanced CT.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CT scanning reduced the rate of negative appendectomies, which, before routine use of CT, was near 20% (12). In a study involving 536 patients with suspected appendicitis, Tamburrini et al found that the sensitivity, specificity, and positive and negative predictive values of non-contrast CT with selective use of contrast were 91.3%, 95%, 82%, and 98%, respectively (13). A recent meta-analysis evaluating the diagnostic accuracy of non-contrast CT for appendicitis found similar results as studies using contrast, with pooled estimate sensitivity and specificity of 92.7% (95% confidence interval 89.5-95%) and 96.1% (95% confidence interval 94.2-97.5%), respectively (14).…”
Section: Discussionmentioning
confidence: 97%